PENGARUH TEMAN SEBAYA TERHADAP PERILAKU BULLYING SISWA - Aminah, Aam; Fitriyah Nurdianah (Jurnal Eksplorasi Bimbingan dan Konseling, 2019)
Cases of bullying in Indonesia often occur in educational institutions. Bullying behavior most often occurs in adolescence. Every child entering adolescence will be faced with social adjustment problems, which include the problem of peer relations. Peers will usually form peer groups. This study aims to: (1) find out the description of peers of students, (2) know the description of student bullying behavior, (3) prove the presence or absence of peer influence on student bullying behavior. The method of this research is quantitative with the type of associative research. The sample of this study was 32 students. The results showed: (1) peers have a high category, (2) bullying behavior in students has a high category, (3) There is a positive influence between peers on student bullying behavior.